Extracorporeal membrane oxygenation in severe respiratory failure resulting from burns and smoke inhalation injury. Issue 5 (August 2018) - Szentgyorgyi, Lajos; Shepherd, Chloe; Dunn, Ken W.; Fawcett, Peter; Barker, Julian M.; Exton, Paul; Maybauer, Marc O.
Abstract: Extracorporeal membrane oxygenation (ECMO) is one of the most frequent forms of extracorporeal life support (ECLS) and can be used as rescue therapy in patients with severe respiratory failure resulting from burns and/or smoke inhalation injury. Experience and literature on this treatment option is still very limited, consequently results are varied. We report a retrospective analysis of our experience with veno-venous (VV) ECMO in burn patients. All five patients, three male and two female (age: 28–37 years) had flame type burns and smoke inhalation injury. Their Murray scores ranged between 3.25 and 3.75, and their revised Baux scores between 62 and 102. The mean pre-ECMO conventional ventilation time was 7.4 days (3–13). The mean ECMO duration was 18 days (8–35). Three patients were cannulated with dual lumen, two with separate cannulae. One oxygenator had to be changed due to technical issues and two patients needed two parallel oxygenators. Four patients had renal replacement therapy. All patients needed vasoconstrictor support, antibiotics and packed red blood cells (5–62 units). Three had steroid treatment. All five patients were successfully weaned from ECMO. One patient died later from multi-organ failure in the ICU, the other four patients survived. VV-ECMO is a useful rescue intervention in patients with burns related severe respiratory failure. Patients in our institution benefit from having both burns and ECMO centres with major expertise in the field under one roof. The results from this small cohort are encouraging, although more cases are needed to draw more robust conclusions.